Estimation of reaction kinetics for aromatic and heterocycles nitration in mixed acids through computational chemistry approach - Jadhav, Pandurang M.; Pandey, Raj K.; Kulkarni, Amol A. (International Journal of Chemical Kinetics, 2021)
Nitration of aromatic compounds and heterocycles in mixed acid environment is one of the regularly performed large-scale reactions in the chemical industry. Although the reaction mechanism of nitration of aromatics in mixed acid is well established, the development of a methodology for the evaluation of kinetics of exothermic aromatic nitrations in a simplified and accurate way is necessary. Here we evaluate the applicability of a kinetic evaluation methodology based on Hammett's acidity function, acidity function, and empirical activity coefficient for the nitration reaction. The contributions from the functional groups on the aromatic ring and quantitative structure-activity relationships technique are considered for these evaluations. Natural bond orbital and magnetic index nucleus independent chemical shift analyses were carried out to obtain the substitution constants. The rate constant and activation energy values were evaluated at various temperatures and sulfuric acid strengths. The results were validated by comparing with the experimental data from the literature for several molecules. The effect of various functional groups (viz carbonyl, carboxyl, methyl, and amine) substituted on the benzene ring was also evaluated. For a few identified substrates, the data were used for estimation of residence time needed for complete conversion in continuous stirred tank reactor and in a plug flow reactor to quantify the effect of substitution constant and strength of sulfuric acid. The approach will help select a suitable reactor.
Keywords: Aromatic nitration; computational chemistry; Hammett analogy; mixed acids; Reaction kinetics; reactor selection